Parallel backpropagation neural network training for face recognition - Omarov B.; Suliman A.; Tsoy A. (Pushpa Publishing House, 2023)
In this paper, we describe implementation of ANN training process using backpropagation learning algorithm for exploiting the high performance SIMD architecture of GPU using CUDA. We also compare sequential and parallel algorithm execution times and conducted speedup analysis for both the methods. The simulation results demonstrate a significant decrease on executing times and greater speedup than serial implementation of training and learning processes. All due to the parallel algorithm and use of the GPU, the training time for huge set of images get reduced significantly increasing the accuracy rate of face recognition. 2016 Pushpa Publishing House, Allahabad, India.